Olanzapine-induced Metabolic Syndrome and its Association with -759C>T Polymorphism of the HTR2C Gene in Iraqi Schizophrenic Patients - Zinah Abdulhameed Alobaidi; Mohammed, Samer Imad (Iraqi Journal of Pharmaceutical Sciences, 2024)
The hazardous metabolic effects of treating schizophrenia patients with olanzapine comprise serotonin 2C receptor (5-HT2C) antagonists. Metabolic side effects of antipsychotic drugs, including lipid abnormalities, disturbed glucose metabolism, and weight gain, can have a major impact on treating psychiatric patients. The intent of this study was to investigate whether there is an associated link between the genetic polymorphism at -759C>T in the promoter region of the 5-hydroxytryptamine 2C receptor (HTR2C) gene and the metabolic syndrome driven by olanzapine in schizophrenia patients. A cross-sectional study that involved fifty hospitalized patients with schizophrenia. The patients were split into two groups (metabolic and non-metabolic) according to the classification criteria of the metabolic syndrome. The HTR2C promoter region polymorphism was identified through sequencing using the Sanger method after polymerase chain reaction amplification of the extracted deoxyribonucleic acid. Even though none of the genotypes of the -759C>T variant are associated with the propensity to develop metabolic syndrome, there is a significant difference in the -759C>T variant's T allele (p-value = 0.001). The presence of the T allele in the -759 C/T variant was significantly associated with developing metabolic syndrome.Keywords: Schizophrenic patients, Olanzapine, Genetic polymorphism, 5-hydroxytryptamine 2C receptor (HTR2C) gene, -759C>T.